Coming back from war: psychosocial support for veterans and their family members - Stoliaryk, Olha; Semigina, Tetyana (Social work and education, 2023)
The Russian-Ukrainian war, which escalated in connection with the full-scale invasion of the aggressor country in February 2022 and the occupation of a large part of the territory of Ukraine, led to an increase in the number of veterans who suffered the trauma of a high degree of intensity due to participation in armed conflicts.The article examines the specifics of the veteran community as a category of social work clients and reveals the methods of providing social support based on an approach focused on clients' strengths. The main stages of veteran psychosocial support inherent in this approach have been determined (1) the mobilization phase; (2) the stage of being in the zone of armed conflicts and hostilities; (3) stage of demobilization, returning home; (4) the stage of reintegration into the community and family, building of formal and informal support networks; (5) the stage of considering new life meanings , taking care of one's own "I", searching for oneself; (6) the stage of normalization of life situation: restoration of routine, activity, return to usual activities.Since traumatic experiences affect not only veterans but also members of the family system as the immediate environment, the psychosocial services provided must be family-oriented and consider the family context as a resource environment that can influence the adaptation process of veterans to peaceful life and return to the family. It is advisable for social workers to choose tools for working with veterans that are not capable of harming their clients and that rely on activating the strengths of individuals and families, to observe the general principles of the strengths-based approach.Ethical risks and obstacles that may arise in the work of a social work specialist, taking into account the specific experience of veterans and complicating the process of applying the strengths perspective, are analyzed.